Prevailing sea surface temperatures inhibit summer reproduction of the kelp Laminaria digitata at Helgoland (North Sea). Issue 6 (18th November 2013) - Bartsch, Inka; Vogt, Johanna; Pehlke, Constanze; Hanelt, Dieter; Buschmann, A.
<x xml:space="preserve">Abstract</x> The impact of abiotic factors on kelp sporophyte reproduction has rarely been investigated. Laminaria digitata (Hudson) J.V. Lamouroux is one of the few summer fertile Laminaria species worldwide and reproduction is subjected to relatively high water temperatures. We investigated the impact of prevailing summer temperatures (~18°C in August) on the induction of sporangia, meiospore release, and germination at the island of Helgoland (North Sea). At Helgoland, fertile sporophytes are found between April and December with a maximum in late summer. While released meiospore numbers were constant between June and October, germination rates decreased significantly in summer. Short‐term exposure of mature sori to 17°C–22°C induced a significantly higher meiospore release indicating enhancement of sporulation by elevated temperatures. Induction of sporangia on vegetative blade disks was not possible at 20°C, and fertility was only 20% at 18°C–19°C, but it was 100% in cool temperatures of 1°C–10°C. It was shown for the first time in a kelp species that "sporogenesis" is the life‐cycle process with the narrowest temperature window compared to growth or survival of the sporophyte or reproduction, growth, and survival of the gametophyte. We incorporated several parameters (induction time, fertile area, and relative fertility) into a "Reproductive efficiency index." This indicates that sporogenesis of L. digitata is a cold‐adapted process with an optimum at (5)–10°C. The results show that the population at Helgoland is at its reproduction limit despite the existence of other geographically more southerly located populations.